(untitled) (Orthodontic Journal of Nepal, 2015)
Introduction: Debonding of ceramic brackets requires a technique that will restore the enamel surface possibly to its pretreatment condition. Objective: To evaluate a comparative degree of enamel loss with various debonding techniques. Materials & Method: 30 extracted premolars were divided into three equal groups of 10 each on the basis of bonding material used. Six subgroups comprising of 5 teeth each were formed on the basis of debonding techniques. Debonded enamel surfaces were photographed under Scanning Electron Microscope to evaluate the enamel loss percentage and compared using oneway ANOVA. Result: Decreasing order of enamel surface loss was 63.1%, 56.3%, 45.4%, 43%, 31% and 30.5% for light cure–mechanical, light cure-electrothermal, self cure-mechanical, self cure-electrothermal, single composite-mechanical and single compositeelectrothermal combination respectively. Conclusion: Mechanical debonding leads to greater enamel loss than electrothermal debonding. Bonding with Light cure composite always leads to greater enamel loss irrespective of type of debonding technique. Bonding with single composite always leads to lesser enamel loss irrespective of debonding technique.